Web page and health communication: experience report in scientific initiation project - Wolff Machado, Vanessa; Tavares Ribeiro, Mateus; Yuri Gonçalves Silva, Marlon (Seven Editora, 2023)
Introduction: The work of the Toxicological Information and Assistance Center depends on effective health communication. Information and communication technologies have the potential to improve information management, access to health services, quality of care, continuity of services and cost containment.  Objectives: Experience report of the process of implementing the website as a communication tool in health by students and their advisor in the Scientific Initiation Program.  Method: Descriptive, qualitative study, of the experience report type.  Discussion: The article exposes the authors' motivations with a contextualized report, with objectivity and theoretical support. From the confrontations and difficulties within the project journey, solutions and new paths were pointed out. Conclusion: Although the initial objective proposed was not feasible within the bureaucratic procedures and stipulated deadlines, it was possible to point out the relevance of the work and its lessons. DOI: https://doi.org/10.56238/tfisdwv1-087